Financial analysis of yellow maize farm on ex-teak forest land (Case in Wakadia Village, Watopute District, Muna Regency, Southeast Sulawesi) - Alimin, Alimin; Ibin, Darbin (Sangia Research Media and Publishing, 2023)
Yellow maize is an important commodity in the national food security system. Wakadia Village is the largest producer of yellow maize in Watopute District, Muna Regency, Southeast Sulawesi Province. The yellow maize farming cultivated on state land that was ex-teak forest. The aim of the research is to analyze the financial performance of yellow maize farming on ex-teak forest land in Wakadia Villag on its profits and feasibility aspects. The research is conducted on July to August 2022. Population of the study was 414 units yellow maize farming those are cultivated during rainy planting season on 2021 year. Its sample size is 40 units farm. Sampling used multistage cluster sampling technique. Collecting the data used face-to-face interview techniques with every owner of the farming samples. Analyzing the data used quantitative descriptive techniques, including cost analysis, revenue analysis, income analysis, and R/C analysis. The results of the research show that the financial performance of yellow corn farming on former teak forest land in Wakadia Village achieved an average income of Rp. 4,448,350.57/ha, R/C = 1.42 so it is profitable and worthy to be developed.